2022
DOI: 10.1002/pam.22346
|View full text |Cite
|
Sign up to set email alerts
|

Does Temporary Mortgage Assistance for Unemployed Homeowners Reduce Longer‐Term Mortgage Default? An Analysis of the Hardest Hit Fund Program

Abstract: Economic crises like the Great Recession and the COVID pandemic prompt government intervention to stabilize homeowners and housing markets. During the Great Recession, the primary intervention was permanent loan modifications, with mixed evidence of success. The COVID pandemic spurred a more targeted but temporary intervention-mortgage payment relief for unemployed homeowners. Little is known about the long-term effectiveness of temporary mortgage assistance for homeowner outcomes. This paper leverages data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Ohio's program was singled out as a program with substantial delays. Research indicates that, despite lower than intended take-up rates and delays, those who did receive HHF assistance were 40 percent less likely to experience foreclosure on their homes three years after rolling off assistance (Moulton et al 2022).…”
Section: S T U Dy C O N T E X Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohio's program was singled out as a program with substantial delays. Research indicates that, despite lower than intended take-up rates and delays, those who did receive HHF assistance were 40 percent less likely to experience foreclosure on their homes three years after rolling off assistance (Moulton et al 2022).…”
Section: S T U Dy C O N T E X Tmentioning
confidence: 99%
“…In our LPM specification, the reforms are associated with a 2.8 percentage point (19 percent) reduction in the probability of foreclosure. This is a substantive reduction in foreclosure: a prior study found that the receipt of HHF assistance was associated with a 40 percent reduction in the probability of mortgage default and foreclosure (Moulton et al 2022). Reduced administrative burdens thus increased the probability that individual who started the application and who may have otherwise experienced foreclosure ultimately received HHF assistance, thereby reducing the probability of foreclosure for the entire applicant pool.…”
mentioning
confidence: 95%